EVALUATION OF EMONC (EMERGENCY OBSTETRIC AND NEONATAL CARE SERVICES IN BASRAH) FOR FIVE YEARS INTERVAL (2016-2020) - ALABRAHIM MAISAA; AL-IBRAHEEM FATIMAH (Scholar Express Journals, 2022)
Maternal mortality and severe maternal morbidity are critical health issues in Iraq, Maternal mortality ratio per 100000 live birth (34.2) and Neonatal mortality rate per 1000 live births(13.7) in a year 2020 in Iraq, a majority of pregnancy-related deaths are preventable, FANC, along with family planning, skilled delivery care and emergency obstetric care plays an important role in reducing maternal and neonatal mortality.
Keywords: Emergency Obstetric and Newborn Care; Evaluation; maternal mortality